Optimization of high-speed railway station location selection based on accessibility and environmental impact - Sandeepan Roy; Avijit Maji (Asian Development Bank Institute (ADBI), 2019)
High speed railway (HSR) planners aim to select locations that optimize the overall utility or benefit of HSR stations by satisfying various desirable requirements. Among other factors, accessibility and environmental impact are important considerations for HSR station location selection. The desirable requirements of these two factors include improved access to, and intermodal integration with, existing transportation facilities and services (like airports, train stations, and bus stops); avoidance of environmentally sensitive areas (such as water bodies, wetlands, and forest) and land with higher right-of-way costs; and accommodation of strategic necessities (for example, proximity to city centers and socioeconomic development hubs). This study quantifies the overall utility of an HSR station by analyzing the extent to which a location satisfies these desirable requirements. For this, suitable utility functions were developed and evaluated. To obtain individual utility scores, appropriate weights were assigned based on relative importance. The overall utility of a location was then estimated as the weighted summation of these utility scores. A GIS-based analytical framework was specifically developed for geo-processing, mapping, and visualization of the geospatial data analysis and result representation. This utility-based quantification and identification process would be useful to planners in assessing an area and determining the most suitable station locations for an HSR project. The proposed model was used to identify the potential station locations along the Mumbai-Ahmedabad HSR corridor in India and to compare the obtained results with the planned locations of the project.
Keywords: L92; R11; R41; R58; 330; high-speed rail stations; geographic information systems; environmental impact; accessibility; utility functions